Combine Shot Penning (SP) and Ultrasonic Impact Treatment (UIT) for Soil Corrosion Buckling Strength Enhancement of AA 2014-T4 - Al-Alkawi, Hussain J. Mohamed; Faris, Saad T.; Naji, Salam Nihad (Al-Nahrain Journal for Engineering Sciences, 2020)
The aim of this work is to investigate the effect of soil corrosion on the critical buckling load of circular columns made of 2014-T4 aluminum alloy. In this work, 24 specimens were used and buried in the soil for 120 days. The samples divided into two groups (12 columns with corrosion before shot penning (SP) and ultrasonic impact treatment (UIT), and 12 columns with corrosion after combined surface treatments (SP+UIT)). The experimental1results revealed1that the corrosion negatively1affects the mechanical properties1of the material, and the1reduction percentage (R%) for1ultimate tensile strength (UTS) and1yield strength (YS) was (1.95% and 4.57%) respectively. After combined surface treatments (SP+UIT) for the corroded columns, the ultimate1tensile strength (UTS) and yield1strength (YS) were improved with (2.42%, and 2.87%) respectively. Perry-Robertson, Rankine, and ANSYS were used to estimate the critical buckling load (Pcr) and compare it with the experimental results. Rankine and Perry’s formulas have been achieved a good agreement with the experimental without and with (1.5) factor of safety respectively. While ANSYS gave satisfactory prediction with a safety factor of (2.2, and 2.7) and (1.9, and 2.7) for long and intermediate columns before and after (SP+UIP) respectively.